2016
DOI: 10.1039/c6cp06732h
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure and spin states of 2D graphene/VX2 (X = S, Se) heterostructures

Abstract: The structural, magnetic and electronic properties of 2D VX (X = S, Se) monolayers and graphene/VX heterostructures were studied using a DFT+U approach. It was found that the stability of the 1T phases of VX monolayers is linked to strong electron correlation effects. The study of vertical junctions comprising of graphene and VX monolayers demonstrated that interlayer interactions lead to the formation of strong spin polarization of both graphene and VX fragments while preserving the linear dispersion of graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 36 publications
7
38
0
Order By: Relevance
“…4(b). According to DFT calculations, while 1T-VSe 2 is a pure metal, 2H-VSe 2 takes a semimetal behavior in which, considering spin-up or spin-down bands separately, a narrow band gap can be assigned to this phase of VSe 2 [48,49]. Looking back to the absorption responses of the NPs' and NSs' solutions, one can clearly find that the absorption of VSe 2 NPs has been extended above 700 nm, while this response is limited to wavelengths below 360 nm for the case of NSs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4(b). According to DFT calculations, while 1T-VSe 2 is a pure metal, 2H-VSe 2 takes a semimetal behavior in which, considering spin-up or spin-down bands separately, a narrow band gap can be assigned to this phase of VSe 2 [48,49]. Looking back to the absorption responses of the NPs' and NSs' solutions, one can clearly find that the absorption of VSe 2 NPs has been extended above 700 nm, while this response is limited to wavelengths below 360 nm for the case of NSs.…”
Section: Resultsmentioning
confidence: 99%
“…Bulk VSe 2 is a layered compound whose crystal structure is based upon strongly covalent (intralayer) Se-V-Se bonds within each layer and weak van der Waals (interlayer) Se…Se interactions in between. Compared to other types of TMDs, the existence of an overlap between the valance band (VB) and conduction band (CB) of VSe 2 makes this material a pure metal, and it possesses a high level of electrical conductivity that is a key factor in optoelectronics applications [47][48][49]. Besides the extra-high electrical conductivity of a VSe 2 monolayer (that has been experimentally proved recently [47]), some other unexpected properties of this material have also been investigated in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…From the temperature dependent magnetic studies, a saturation magnetization of ≈15μ B is observed and DFT calculations revealed that in monolayer VSe 2 bond spin polarization between V and Se is the origin of the intrinsic ferromagnetic ordering. [ 81,109,110 ] Asreported by Fuh et al, the monolayer VS 2 and VSe 2 were studied, with increasing the number of layers. These VS 2 and VSe 2 monolayers are found to be ferromagnetic, known as ferromagnetic insulators.…”
Section: Structure and Properties Of Vx2mentioning
confidence: 99%
“…VX 2 ‐based materials are known for its metallic nature and most of them are reported to show zero bandgap at room temperature. [ 38,110 ] Due to the absence of optical bandgap, it has been expected that VX 2 ‐based materials should not be considered for optical applications. However, H‐VSe 2 is encountered to have a small optical bandgap of ≈0.8 eV between the valence band maximum and conduction band minimum by considering the spin‐up and spin‐down bands separately.…”
Section: Structure and Properties Of Vx2mentioning
confidence: 99%
“…This result is consistent with the predictions made through first principle simulations that both semiconducting 1H and metallic 1T phases of monolayer transition‐metal dichalcogenides (TMDC) exhibit FM ordering with in‐plane magnetization direction. [ 96,98,99 ] This strong magnetic anisotropy resulting in‐plane spin polarization in TMDC monolayers mainly originates from both through‐bond and through‐space interactions between transition metal and chalcogenide ions. [ 96 ] The experimental demonstration of intrinsic magnetism has already extended to various other transition metal compound monolayers such as itinerant ferromagnetism in 1T‐MnSe2, [ 100,101 ] Fe 3 GeTe 2 , [ 102 ] Cr 2 Ge 2 Te 6 , [ 103 ] TM dihydride MH 2 (M = Sc,Co), [ 104 ] and electric filed controlled magnetism in Fe 3 GeTe 2 , [ 105 ] Cr 2 Ge 2 Te 6 , [ 103 ] and bilayer CrI 3 .…”
Section: Origin Of Ferromagnetism In Qah Systemsmentioning
confidence: 99%